Comparing the effects of long-term vs. periodic inclusion of isometric strength training on strength and dynamic performances - Lum, D.; Joseph, R.; Ong, K. Y.; Tang, J. M.; Suchomel, T. J. (The Journal of Strength and Conditioning Research, 2023)
This study compared the effects of including isometric strength training (IST) for consecutive 24 weeks (CIST) against a periodic inclusion (PIST) of this mode of training on strength and dynamic performances. Twenty-four floorball athletes (age: 23 ± 2.7 years, stature: 1.74 ± 2.08 m, and body mass: 72.7 ± 14.4 kg) were randomly assigned to the control (CON), CIST, or PIST group. Athletes completed 20-m sprint, countermovement jump (CMJ), and isometric midthigh pull (IMTP) during pre-test and were tested on weeks 6, 12, 18, and 24. All groups performed a similar strength training program twice per week. However, 2 sets of squats were replaced with isometric squat in CIST for all 24 weeks but only on weeks 1-6 and 13-18 for PIST. A significant main effect for time was observed for 5-, 10-, and 20-m sprint time, CMJ height, peak force, peak power, time to take-off, modified reactive strength index, IMTP peak force, relative peak force, and force at 200 milliseconds (p = <0.001-0.037). Isometric strength training for 24 consecutive weeks resulted in greater improvement in 5-m sprint time than CON at week 24 (p = 0.024, g = 1.17). Both CIST and PIST resulted in greater improvements in 10-m sprint time than CON at various time points (p = 0.007-0.038 and 0.038, g = 1.07-1.44 and 1.18, respectively). Isometric strength training for 24 consecutive weeks and PIST resulted in greater improvements in 20-m sprint time than CON at week 6 (p = 0.007 and 0.025, g = 1.65 and 1.40, respectively). The results showed that the inclusion of IST resulted in greater improvements in sprint performance than CON but no significant difference in all measured variables with PIST.